Transcription termination in vitro at the tryptophan operon attenuator is controlled by secondary structures in the leader transcript. - Stroynowski, I (1983)
The role of alternative RNA secondary structures in regulating transcription termination at the attenuator of the tryptophan (trp) operon of Serratia marcescens was examined in vitro by transcribing mutant DNA templates having deletions of different segments of the trp leader region. Deletions that removed sequences corresponding to successive segments of postulated RNA secondary structures either increased or decreased transcription termination at the attenuator. The results obtained are consistent with the hypothesis that transcription termination results from RNA polymerase recognition of a particular RNA secondary structure, the terminator. This structure forms only in the absence of an alternative, preceding, RNA secondary structure, the antiterminator.